Disentangling and Closing the Nutrient-Based Potato Yield Gap Using Integrated Nutrient Management Under Temperate Environments of Sub-Saharan Africa - Jabulani Ntuli; Nomali Ziphorah Ngobese; Lucky Sithole; Sandile Hadebe (Horticulturae, 2025)
Closing the nutrient-based potato yield gap in sub-Saharan Africa (SSA) remains a major challenge due to low fertilizer use, degraded soils, and rising temperatures that exacerbate nutrient losses. Field experiments were conducted over two growing seasons to investigate the causes of the potato nutrient-based yield gap and develop an integrated nutrient management (INM) strategy aimed at narrowing this gap. Integrated nutrient management factors included three fertilizer application rates [no fertilizer (control), 50%, and 100% of recommended fertilizer application rates], two soil cover levels (grass mulch applied and absent), and four potato cultivars (Mondial, Sababa, Panamera, and Tyson). The study identified a substantial yield gap of 42–45 t/ha, largely driven by insufficient fertilizer application and poor nutrient retention. Integrating full recommended fertilizer rate, mulching, and Panamera closed up to 84% of this gap, achieving a yield of 43 t/ha. Notably, reduced fertilizer application combined with mulching and Panamera maintained high yields (35–41 t/ha), indicating that resource-efficient practices can sustain productivity. These findings underscore the importance of coupling judicious fertilizer use with nutrient loss-mitigating and nutrient uptake-enhancing strategies. Further research is needed to address the residual yield gap and assess the economic feasibility of INM adoption under potato farming conditions in SSA.